(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study sought to establish the impact of Training and Development on Employee productivity in public Universities a case of Masinde Muliro University of Science and Technology. The target population was drawn from non-teaching staff by use of simple sampling. A sample of 69 employees was selected through simple sampling to participate in the study. The researcher used purposive random sampling and sampled every non-academic staff in the payroll from grade I-X. The research targeted a total of 676 non-academic staff. Data was collected by use of questionnaires. The study used both descriptive and inferential statistics during data analysis. Descriptive statistics employed the use of frequencies and percentages and for inferential statistics Pearson Correlation Coefficient of 90% confidence was used and findings presented in tables. Results showed that there was a significant negative relationship between gender awareness, training policy where every staff is aware with the value of r(69) = -0.301, p = 0.01 and also responses on training policy of which every staff is aware had a significant negative relationship in experience on their current grade, r(69) = -0.207, p = 0.09. More than 50% of the respondents agreed that training and development affects employee productivity and the results were mostly more significant between training and development factors and gender, age, length of service and current grades among University employees.